2019
DOI: 10.2188/jea.je20180123
|View full text |Cite
|
Sign up to set email alerts
|

Bathing Frequency and Onset of Functional Disability Among Japanese Older Adults: A Prospective 3-Year Cohort Study From the JAGES

Abstract: BackgroundWhile bathing styles vary among countries, most Japanese people prefer tub bathing to showers and saunas. However, few studies have examined the relationship between tub bathing and health outcomes. Accordingly, in this prospective cohort study, we investigated the association between tub bathing frequency and the onset of functional disability among older people in Japan.MethodsWe used data from the Japan Gerontological Evaluation Study (JAGES). The baseline survey was conducted from August 2010 thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…We included a wide range of covariates in the analyses as potential confounders based on prior literature. 8 , 9 , 12 , 18 , 21 Information on sex, age, hypertension, diabetes mellitus, smoking habit, alcohol intake, family structure, social participation, depressive symptoms, cognitive function, instrumental activities of daily living (IADL), educational attainment, and equivalent income was obtained from a self-administered questionnaire. Smoking habit and alcohol intake were classified into the following three categories: current, ever, and never.…”
Section: Methodsmentioning
confidence: 99%
“…We included a wide range of covariates in the analyses as potential confounders based on prior literature. 8 , 9 , 12 , 18 , 21 Information on sex, age, hypertension, diabetes mellitus, smoking habit, alcohol intake, family structure, social participation, depressive symptoms, cognitive function, instrumental activities of daily living (IADL), educational attainment, and equivalent income was obtained from a self-administered questionnaire. Smoking habit and alcohol intake were classified into the following three categories: current, ever, and never.…”
Section: Methodsmentioning
confidence: 99%
“…Yagi et al showed that a high frequency of bathing (≥7 times/week) was associated with a lower risk of functional disability compared to a low frequency of bathing (0 to 2 times/week) [ 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…Bathing disability has been independently associated with an increased likelihood of long-term nursing home admission [ 43 ] and is a primary indicator of the need for home care services [ 44 ]. Japanese people generally prefer to take baths rather than taking showers or sauna baths not only for cleanliness but also to feel warm and refreshed as well as to aid in sleep [ 45 ]. Morris et al reported that individuals receiving home care in Hong Kong had the highest rate of grooming disabilities [ 22 ].…”
Section: Discussionmentioning
confidence: 99%